Landscape valuation based on the ecological requirements of ‘Tayassu pecari ‘ and ‘Tapirus terrestris’ – a forest with araucaria, in Paraná state, Brazil - Vidolin, Gisley Paula; Batista, Daniela Biondi; Wandembruck, Adilson (Ciência Florestal, 2011)
This study valuated the landscape of Lageado Grande farm (LGF), an area of 3,136.32 ha, located in General Carneiro, Palmas, and Bituruna, Paraná state, Brazil. The evaluation was based on an integral analysis of the ecological requirements of Tayassu pecari and Tapirus terrestris and the functional aspects of the LGF landscape. Land use and land cover were mapped, and the map was divided into 335 grids of 10 ha each, which were scored with pre-defined criteria. The scores of each aspect were integrated by multiplying the values and calculating the standard deviation and the mean to establish the classification intervals of the general quality of the landscape. The class gradient for the survival and the preservation of the analyzed species generated was: extremely important, very important, important, and of little importance. It was observed that 61.2% of LGF has environments relevant to the preservation of the species, composed by a forest predominantly of pine, broadleaves, lowlands, and some riparian forest patches of Iratim River. The results show that LGF comprises a mosaic of environments suitable for the occurrence and maintenance of these ungulates.